Segmenting your data for maximum customer insight - Robinson, Mark (Henry Stewart Talks, 2008)
What is a behavioral classification/segmentation, The marketing database journey, Different types of segmentation, Behavioral segmentations based on clustering, Financial services segmentation example, Best practice rules, How to define key business measures such as profitability and potential, Income to date from current product holdings, Income to come from current product holdings, Mortgage NPV curve, Income to come from new product holdings, Customer profitability by decile (% profit), Most and least profitable customers, Customer segmentation, Segment strategies within the framework, How to get the business to take advantage of the findings and add value to communications planning and brand development